UMKM DAN PEMBANGUNAN - Muhammad Rafi Andhera; Muhammad Addnan Nur Nasution (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
MSME is an abbreviation for Micro, Small and Medium Enterprises. MSMEs are the meaning of businesses or businesses carried out by individuals, groups, small business entities, or households. Indonesia as a developing country makes MSMEs the main foundation of the community's economic sector. This is done to encourage the ability to develop independence in society, especially in the economic sector. The development of MSMEs in Indonesia continues to increase in terms of quality, this is due to strong support from the government in the development carried out for MSME business activists, which is very important in anticipating future economic conditions as well as maintaining and strengthening the structure of the national economy. Development in the era of globalization is very dependent on the economic sector as a measure of success carried out by the government. The role of society in national development, especially in economic development, is Micro, Small and Medium Enterprises (MSMEs). The position of MSMEs in the national economy has an important and strategic role. This condition is very possible because the existence of MSMEs is quite dominant in the Indonesian economy. MSMEs after the economic crisis continue to increase from year to year. This also proves that MSMEs are able to survive in the midst of an economic crisis. MSMEs have also been proven to absorb a larger workforce in the national economy. By absorbing so many workers, the MSME sector is able to increase people's income. Thus, MSMEs are considered to have a strategic role in reducing unemployment and poverty. For the contribution and role of MSMEs, it is important for the government to continue to support MSMEs through strengthening so that their role as pillars in building the nation's economy can run optimally